Counseling on the Role of Couples of Childbearing Age as Aseptopes for Family Planning in Neighborhood V, Kelurahan Baru Ladang Bambu, Kec. Lucky Field in 2021 - Helena Fransysca; Emelia A. Tampubolon (Science Midwifery, 2021)
The purpose of this study was to find out whether there were benefits from the effect of doing pregnancy exercise on low back pain in pregnant women. And the activities carried out are increasing the knowledge of pregnant women about pregnancy exercise to reduce low back pain during pregnancy, increasing the knowledge of husband or family to assist mothers in routine pregnancy check-ups, helping to give the role of husbands to the implementation of pregnancy exercises to reduce maternal low back pain during pregnancy. pregnancy. The types and forms of activities of this activity are to provide material to pregnant women, husbands or accompanying families about the importance of pregnancy exercise during pregnancy to reduce maternal low back pain during pregnancy, and to help mothers to facilitate the delivery process. carry out free pregnancy check-ups, provide nutritious food for pregnancy. The results of the study are To achieve the objectives of the above activities, activities were carried out including the delivery of material about the benefits of pregnancy exercise to reduce low back pain in pregnant women during pregnancy.